Implementasi Kombinasi Algoritma Kriptografi Menggunakan Atbash dan Caesar Cipher Pada Nilai Rapot Akhir Siswa MA Berbaur di Wonosobo - Mukhamad Ulul Albab; Muhammad Imron Rosadi (Jurnal ICT: Information Communication & Technology, 2025)
The development of information technology demands an improvement in data security systems, especially in the world of education which stores a lot of sensitive information such as student report card grades. This study aims to design and implement a cryptographic system combining the Caesar Cipher and Atbash Cipher algorithms to improve protection of students' final report card data at Madrasah Aliyah (MA) Berbaur Wonosobo. The Caesar Cipher method is used to encrypt letter-based data through a fixed character shift, while the Atbash Cipher is applied to numeric data with digit substitution based on the vertical position in the number sequence. The combination of these two methods produces a more complex and secure layered encryption system. This study uses a software engineering approach with implementation methods and system testing. The implementation results show that the combination of algorithms is able to maintain the integrity and confidentiality of student report card data effectively, and can be used as an applicable and efficient academic data security solution.